mãi mới ra gê qá X_X pt<=>Sin3x+Cos3x−2Sinx=2√2(1−4sin2x)<−>Sin3x−Sinx−Sinx+Cos3x=2√2(1−4(1−Cos2x))<−>2Cos2xSinx−Sinx+Cos3x=2√2(4Cos2x−3)<−>Sinx(2Cos2x−1)+Cos3x=2√2(4Cos2x−3)<-> Sinx[2(2Cos2x−1)−1)+Cos3x=2√2(4Cos2x−3)<−>(Sinx−2√2)(4Cos2x−3)+Cosx3=0xét với cosx khác O <->$(Sinx-2\sqrt{2})Cos3x+Cos3xCosx=0 $$<->Cos3x(Sinx+Cosx-2\sqrt{2})=0$<->$Cos3x=0 (do Sinx+Cosx-2\sqrt{2})=0 vô n)$(à còn th Cosx= O hình như ko là nghiệm hay sao ấy bạn kiểm tra lại giúp mình )
mãi mới ra gê qá X_X
pt<=>Sin3x+Cos3x−2Sinx=2√2(1−4sin2x)
<−>Sin3x−Sinx−Sinx+Cos3x=2√2(1−4(1−Cos2x))<−>2Cos2xSinx−Sinx+Cos3x=2√2(4Cos2x−3)<−>Sinx(2Cos2x−1)+Cos3x=2√2(4Cos2x−3)<->
Sinx[2(2Cos2x−1)−1)+Cos3x=2√2(4Cos2x−3)<−>(Sinx−2√2)(4Cos2x−3)+Cosx3=0$<->(Sinx-2\sqrt{2})
(4Cos
^2x-3
)+Cos
(4Cos
^2x
-3)=0$$<->(
4Cos
^2
x-3
)(Sinx+Cosx
-2\sqrt{2})=0$